It’s Like Telling People You Have Rats and Forgetting to Qualify Them as Pets: A Poet's Journey (LEARNing Landscapes, 2011)
How do I take my place as a learner, parent, educator in the fractal, multifaceted, kaleidoscopic process of being and becoming? How to negotiate the forces that pull us and push us in different directions? Or, how I discovered I am a poet, and survived to tell of it.
Keywords: learner; parent; educator; poet; inquiry